STUDY OF THE BEST PINE PLANTATIONS AND SELECTION OF PLUS TREES IN THE ZAPORIZHZHYA REGION - Tereshchenko, L. I. (Forestry and Forest Melioration, 2018)
Introduction In the Zaporizhzhya region, the percentage of forest land is the lowest among the Ukrainian regions and amounts 3.7 %. Тhe optimal value of the forest land percentage is 5.3 %. For purposes of recreation, it should be 12–15 %. Erosion, salinization, alkalinization of soil, compaction, flooding, disturbance, landslides – all these types of land degradation are specific for the Zaporizhzhya region. Degradation of forests occurs due to adverse climatic conditions, industrial influences of large enterprises, and recreational load. The total area of forest lands in the region is 118.9 thousand hectares, of which 76.8 thousand hectares are in the state forest fund. As of January 1, 2016, the area of Zaporizhzhya region covered with forest vegetation amounted to 35.2 thousand hectares. Plantations of the enterprises subordinated to Zaporizhzhya Regional Department of Forestry and Hunting include over 70 tree species. According to forest surveys in 2011, pine forests account for 9 % of land covered with forest vegetation. An increase in the percentage of forest land requires the provision of forestry enterprises with more seeds and planting material with improved properties. To increase the productivity of the existing objects of the permanent forest-seed establishment and its expansion, the State Forest Resources Agency of Ukraine approved "The Program for the Development of the forestry seed collection and storage for 2010–2015" in 2010. The purpose of the presented study was to describe the best plantations of Scots pine (Pinus sylvestris L.) and Crimean pine (Pinus nigra subsp. Pallasiana (Lamb.) Holmboe) in the Zaporizhzhya region. Also, we attempted to highlight the results of the selection of plus trees in these plantations in 2012. Materials and Methods In order to select plus trees, eight best pine plantations were surveyed in five forestry enterprises in the region. Sample plots were established in six of them. At the sample plots, we described the available understory and underbrush and estimated the coverage abundance using the scale of Vysotsky. To estimate trees for candidates for plus trees the dbh (the diameter of a tree measured 1.3 m above ground level), the height of the tree, the height of the stem to the first lower living and dead branches, the diameter of the crown, selection category, health condition, and available defects and damage have been determined. For candidates for plus trees, we calculated the increase in height and diameter over the average values at the stand and the length of the branchless part of the stem. For the determination of selection category of the tree the modified scale of Veresin was used. The pine plantations of the region are limited and presented mainly by Crimean pine. The investigated stands were aged 38–79. The plots were located in dry and fresh fairly infertile sites. The height above sea level was 70-81 m. Results The plantations of Scots pine with the Crimean pine added were highly productive (first yield class) in Zaporizke and Kamyansko-Dniprovske Forestry Enterprises. Four Crimean pine plantations in other forestry enterprises grew according to the third yield class. The health of Scots pine stands was usually good (2.1 and 2.3 points), for Crimean pine, from satisfactory (3.4 points) to good (2.3 points). The selection structure was the best in 79-year-old Crimean pine stand, where the normal trees (62 %) dominated and 23 % was assigned to the I and II selection categories. However, as a result of climatic changes and a significant age of trees, the weakening of this stand was noted. About half of the Scots pine trees in mixed plantations had stem defects, such as sweeps, lateral shoot, and forks. Most pine plantations had from 0 to 16 % of the plus trees of the II category. The pine trees were found to be better naturally pruned in a dry ecotope, in contrast to fresh one. The total understory projective cover of the plots was from 2 to 15 %. The projective cover for the underbrush was from 10 to 30 %. Among hardwoods, the most common are Quercus, Acer, and Robinia. The understory is complemented by Ulmus, Celtis, Gleditsia, Plаtanus. In half of the plots, the pine self-seeding was found. However, it was unable to develop into a new forest stand. According to the survey results, seventeen plus trees of Scots pine (two forestry enterprises) and forty-five trees of Crimean pine (five forestry enterprises) were selected. The selected trees were certified and included into the State Register in order to preserve the gene pool of these species. Seventeen selected plus trees exceeded the average indices of Scots pine plantations by 7.6 % in height and by 5.3 % in diameter on average; the branchless part of the stem was on average 24.7 % longer. Plus trees of the Crimean pine (45 trees) were characterized by the following average exceeding of the indices: 13.5 % in height, 26.7 % in diameter and 35.3 % in the average height of the branchless part of a stem. As more than 30% excess in the average diameter was noted only for the selected trees in the 79-year-old plantation, it is proposed to reduce the criterion for plus trees selection for steppe conditions by the index. It was found that the height excess is directly related to the soil moisture (r = 0.57). Conclusions Among the investigated 38–79-year-old pine plantations grown in five forest enterprises of the Zaporizhzhya region the most favorable conditions for the growth of Scots and Crimean pines are on the terraces in the Dnieper River valley. About half of the Scots pine trees in mixed stands had defects of stems. The stems of the Crimean pine were of better quality. The oldest Crimean pine plantation has shown to be the best in the breeding structure but due to climate change and a significant age of trees there was weakening of the stand. Seventeen Scots pine plus trees and forty-five Crimean pine plus trees of the II selection category have been selected in the six plantations of Zaporizhzhya region. The excess of growth indices of selected Scots pine trees over the average values of the plantations was lower as compared to that of Crimean pine trees: on average by 44 % in height and by 80 % in diameter. The length of the branchless part of the stem in the selected trees of Crimean pine was on average one third higher than that of the Scots pine trees. It is proposed to change the criterion of plus trees selection for steppe conditions by diameter: to reduce the exceedance index from 30 % to 15–20 %. 3 Figs., 3 Tables, 11 Refs.